Natural convection in nanofluids: Are the thermophoresis and Brownian motion effects significant in nanofluid heat transfer enhancement? - Haddad, Zoubida; Abu-Nada, Eiyad; Öztop, Hakan Fehmi; Mataoui, Amina (Elsevier France-Editions Scientifiques Medicales Elsevier, 2012)
Natural convection heat transfer and fluid flow of CuO-Water nanofluids is studied using the Rayleigh-Benard problem. A two component non-homogenous equilibrium model is used for the nanofluid that incorporates the effects of Brownian motion and thermophoresis. Variable thermal conductivity and variable viscosity are taken into account in this work. Finite volume method is used to solve governing equations. Results are presented by streamlines, isotherms, nanoparticle distribution, local and mean Nusselt numbers and nanoparticle profiles at top and bottom side. Comparison of two cases as absence of Brownian and thermophoresis effects and presence of Brownian and thermophoresis effects showed that higher heat transfer is formed with the presence of Brownian and thermophoresis effect. In general, by considering the role of thermophoresis and Brownian motion, an enhancement in heat transfer is observed at any volume fraction of nanoparticles. However, the enhancement is more pronounced at low volume fraction of nanoparticles and the heat transfer decreases by increasing nanoparticle volume fraction. On the other hand, by neglecting the role of thermophoresis and Brownian motion, deterioration in heat transfer is observed and this deterioration elevates by increasing the volume fraction of nanoparticles. (C) 2012 Elsevier Masson SAS. All rights reserved.
Keywords: Natural convection; Brownian; Thermophoresis; Nanofluid